2021
DOI: 10.1055/s-0041-1726304
|View full text |Cite
|
Sign up to set email alerts
|

Proving Triptycene Homoconjugation with the Same Chromophore but Different Connectivity to the Core

Abstract: Homoconjugation is a phenomenon discussed for various π-systems where classical conjugation is broken by e.g. methylene units but still a stabilization by electronic communication exists. In this respect, triptycene with its rigid C3 symmetric geometry is an ideal scaffold to study this phenomenon. Although several studies based on triptycene strengthen the hypothesis of homoconjugation, in all described cases the electronic communication through space relies on different π-blades. Here, two triptycenes are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…39,40 Recent articles from the Mastalerz group which provides both reference to other key articles that led to this conclusion, alongside further experimental evidence of homoconjugation in triptycene derivatives. 41,42 Since these studies, numerous other molecules were synthesised which clearly displayed the influence of homoconjugation, however it is only in recent years that this phenomenon has begun to be employed deliberately to exert control over the photophysical and electrochemical properties of triptycenes for optoelectronic applications. This review will focus on homoconjugation effects in triptycenes in this context.…”
Section: Homoconjugation In Triptycenementioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Recent articles from the Mastalerz group which provides both reference to other key articles that led to this conclusion, alongside further experimental evidence of homoconjugation in triptycene derivatives. 41,42 Since these studies, numerous other molecules were synthesised which clearly displayed the influence of homoconjugation, however it is only in recent years that this phenomenon has begun to be employed deliberately to exert control over the photophysical and electrochemical properties of triptycenes for optoelectronic applications. This review will focus on homoconjugation effects in triptycenes in this context.…”
Section: Homoconjugation In Triptycenementioning
confidence: 99%
“…39,40 Recent articles from the Mastalerz group which provides both reference to other key articles that led to this conclusion, alongside further experimental evidence of homoconjugation in triptycene derivatives. 41,42…”
Section: Introductionmentioning
confidence: 99%
“…Homoconjugation in triptycene was first postulated in 1950, [28] and proven in 1983 by photoelectron spectroscopy in alliance with quantum‐chemical calculations [29] . Further studies by the Mastalerz group confirmed the importance of homoconjugation [30,31] . Several studies already inspected the electronic coupling between redox‐active fins in partially oxidized triptycene derivatives.…”
Section: Introductionmentioning
confidence: 97%
“…[29] Further studies by the Mastalerz group confirmed the importance of homoconjugation. [30,31] Several studies already inspected the electronic coupling between redox-active fins in partially oxidized triptycene derivatives. For example, Iwamura and Makino synthesized a triptycene-type compound with two benzoquinone units.…”
Section: Introductionmentioning
confidence: 99%
“…Triptycene (Figure 1) is another three‐dimensional polycyclic molecule which has a much more rigidly defined structure than TCAQ with covalent bonds rather than steric interactions enforcing its propeller‐like structure. This structure can facilitate electronic communication between the fins through homoconjugation which gives triptycene distinctive optoelectronic properties [21–26] . A small number of triptycene‐fused TCAQs linked to porphyrins have previously been reported as model compounds for studying photoinduced electron transfer, however the descriptions of their electrochemistry do not include comment on whether a multi‐electron reduction was observed [27,28] …”
Section: Introductionmentioning
confidence: 99%